Drums in the deep South - Menzies, William Cameron, 1896-1957; Madison, Guy; King Bros. Productions; Cinetel Films ([Hollywood, CA] : King Bros. Productions, 1951)
Best friends Clay Clayburn and Will Denning graduate from West Point only to soon find themselves fighting on opposite sides of the Civil War. When the two men meet each other in combat, neither knows it as each is in an artillery position hundreds of yards from the other. However, the love of Clay's life, Kathy Summers, does know and tries desperately to save her two good friends from killing each other. --
Based on the story by Hollister Noble.
James Craig, Barbara Payton, Guy Madison.
Cinematographer, Lionel Lindon; editor, Richard Heermance; music, Dimitri Tiomkin.
In English or Spanish.
Online resource; title from opening/closing credits (Digitalia Film Library, viewed August 21, 2015)
Keywords: United States -- History -- Civil War, 1861-1865 -- Drama; Action and adventure films; Historical films; War films; Feature films; Internet videos; Streaming video